Young cosmopolitans and environmental politics: how postmaterialist values inform and shape youth engagement in environmental politics. (3rd July 2022) - Henn, Matt; Sloam, James; Nunes, Ana
ABSTRACT : Many of today's young people are politically engaged and increasingly supportive of progressive political causes. This is most evident in the youth leadership of the Green wave of environmental activism that gathered momentum in 2019. However, we know surprisingly little about the values that drive this mobilisation. In this article, we investigate the link between environmental activism and the emergence of 'young cosmopolitans' as a political force. Using data from the 2017 European Values Study, we analyse the views of 1, 546 18-25-year-olds across ten established European democracies. We find that postmaterialist values, cosmopolitan attitudes and engagement in environmental politics are closely connected; young cosmopolitans are very civically and politically active; and, young environmental activists are particularly likely to be female with high educational attainment levels. Conversely, a significant minority of European youth (disproportionately male with lower educational attainment) are more materialist and nationalist. In the discussion, we explore the role of education and the need to re-think the climate emergency locally – connecting threats to the environment to challenges young people face in their everyday lives. We also explain how the persistence of postmaterialist values amongst younger generations through the Great Recession, suggests that the Green wave will continue post COVID-19.